Gut Microbiome in BALB/c and C57BL/6J Mice Undergoing Experimental Thyroid Autoimmunity Associate with Differences in Immunological Responses and Thyroid Function - Moshkelgosha, Sajad; Masetti, Giulia; Berchner-Pfannschmidt, Utta; Verhasselt, Hedda Luise; Horstmann, Mareike; Diaz-Cano, Salvador; Noble, Alistair; Edelman, Barbel; Covelli, Danila; Plummer, Sue; Marchesi, Julian R.; Ludgate, Marian; Biscarini, Filippo; Eckstein, Anja; Banga, J. Paul (Hormone and Metabolic Research, 2018)
Experimental models of hyperthyroid Graves’ disease (GD) and Graves’ orbitopathy (GO) are efficiently developed by genetic immunisation by electroporation with human thyrotropin hormone receptor (hTSHR) A-subunit plasmid in female BALB/c (H-2d) mice. We investigated susceptibility in C57BL/6 J (H-2b) animals to allow studies on disease mechanisms in transgenic and immune response gene knock-out mice. Higher numbers of female C57BL/6 J were positive for pathogenic thyroid stimulating antibodies, but induced hyperthyroidism remained at a low frequency compared to BALB/c animals. Assessment of hTSHR specific T cells showed reduced proliferation in C57BL/6 J animals accompanied with anti-inflammatory IL-10, with less pro-inflammatory IFN-γ compared to BALB/c. Whilst the orbital tissue from immune BALB/c mice showed inflammation and adipogenesis, in contrast C57BL/6 J animals showed normal pathology. We characterised the gut microbiota using 16 S ribosomal RNA gene sequencing to explore its possible pathogenic role in the model. Despite being housed under identical conditions, we observed significantly different organisation of the microbiota (beta-diversity) in the two strains. Taxonomic differences were also noted, with C57BL/6 J showing an enrichment of Operational Taxonomic Units (OTUs) belonging to the Paludibacter and Allobaculum, followed by Limibacter, Anaerophaga and Ureaplasma genera. A higher number of genera significantly correlating with clinical features was observed in C57BL/6 J compared to BALB/c; for example, Limibacter OTUs correlated negatively with thyroid-stimulating antibodies in C57BL/6 J mice. Thus, our data suggest gut microbiota may play a pivotal immunomodulatory role that differentiates the thyroid function and orbital pathology outcome in these two inbred strains undergoing experimental GO.
Keywords: Graves’ disease; autoimmunity; TSH-receptor antibodies